PENGARUH KOMPETENSI DAN KOMITMEN GURU MATA PELAJARAN EKONOMI TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA JURUSAN IPS DI SMA DAN MA NEGERI SE-KOTA BATU - Weni Sri Wardani; Mardono Mardono; Sri Umi Mintarti (Universitas Negeri Malang, 2015)
The aim of this study was to determine: 1) the influence of teacher competence on student learning outcomes, 2) the influence of teachers' commitment to the learning outcomes of students, 3) the influence of the competence and commitment of teachers to the study of students majoring in social studies on economic subjects in high school MA and SMA in Batu. This study uses a quantitative research approach with descriptive format, the data obtained using a questionnaire instrument controlled with interviews and analyzed with descriptive analysis and multiple linear regression percentage filled by 12 teachers as respondents. The results from this study: there is influence between the competence and commitment of teachers to student learning outcomes either simultaneously or partially. Simultaneously the competence and commitment of teachers has the effect of 92 240% of the learning outcomes of students. Partial influence of teacher competence on student learning outcomes by 44 504%, while the teachers' commitment to the study of students have the effect of 47 736%.